PENGEMBANGAN SISTEM VERIFIKASI MATA KULIAH DENGAN PARSING DATA TEXT TRANSKRIP SIAKAD PADA JURUSAN ILMU KOMPUTER - Astria Hijriani; Dwi Sakethi; Rian Pandu (Jurnal Komputasi, 2014)
In this research, the development of verification systems courses. IT Â aims to accelerate the process of checking the existing curriculum in computer science majors. Course verification systems was developed with the search string matching method which has two parts programming methods: exact matching and heuristic matching. Exact matching programming method using a brute force algorithm has shortcomings because it does not have the preprocessing phase. Meanwhile, heuristic matching algorithm using n-gram similarity as it can check the detail . The results shows brute-force Â algorithm more quickly in running time results. But n-gram similarity algorithm is more efficient in checking if there some difference in one or more character in kopel and course.Keywords: Systems, Verification, transcripts, curriculum, String Matching, Exact Matching, Heuristic Matching, Brute Force, N-gram Similarity.